Development Of E-LKPD Based On Science Literacy Using Liveworksheet On Learning IPAS In Elementary School Students - Resyi A. Gani; Siti Sundari, Fitri; Suryanti, Yanti (Journal of International Multidisciplinary Research, 2025)
The purpose of this study is to develop a science literacy-based E-LKPD for elementary school students and to determine the feasibility of Science Literacy-based E-LKPD using Livework in science learning to improve the understanding of science concepts in grade V elementary school students of SDN Panaragan 2 Bogor City. The method used in this study is the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. This research begins with a needs analysis, making an E-LKPD design, validation by experts, and revising the E-LKPD, after which the E-LKPD is tested on a limited basis and evaluated. The study results show that the effectiveness of E-LKPD based on science literacy has met the criteria very feasible by obtaining a percentage of media experts of 88%, 95% from linguists, and 94% from material experts. Meanwhile, a limited trial conducted on 30 students in class V received a response with a percentage of 93% and a teacher response with a percentage of 92%. Based on these data, it can be concluded that science literacy-based E-LKPD is very feasible to be used by students and teachers as teaching materials on water cycle materials in grade V of Elementary School.